Последний срок: повести и рассказы - Распутин Валентин Григорьевич (Советский писатель, 1985)
Экземпляры: Атабаевская с/б (20231129) / Инвентарный номер: 47871 / Авт.знак: Р 24 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-44